Improving the use of patient-held records in the Emtshezi Subdistrict - T.P. Kerry (South African Family Practice)
Background: The aim of this interventional study was to assess, document and improve the Patient-held Record (PHR) System in the Emtshezi Subdistrict. The study began in 1998 and was conducted using a Quality Assurance (QA) Cycle, which focuses on systems and processes and encourages a team approach to problem solving and quality improvement.1 The keeping of good, accurate health records, as well as the communication of this clinical information between health practitioners, is essential for good quality practice in primary care. In Emtshezi, many patients receive care from different health facilities and practitioners. Historically, the health services in the Subdistrict, as in much of KwaZulu-Natal, were fragmented. Clinics, hospitals and private practitioners in the Subdistrict used a variety of different health records systems, which did not integrate with each other. There was very little communication between these health providers, possibly because no overall plan for health records was worked out for the Subdistrict or the Province at that stage. The Emtshezi Subdistrict forms part of the uThukela Health District of KwaZulu-Natal and lies 120 km northwest of Pietermaritzburg. The population is mostly rural. The major towns are Estcourt, Weenen and Winterton. In the Subdistrict, there is one district hospital of 300 beds, 10 residential clinics and four mobile clinics. There are more than 20 private practitioners, the majority of whom practice in Estcourt. The term “ambulatory records” refers to records that are used by outpatients as opposed to records used for admission to a hospital ward. Two basic types of ambulatory medical records are used throughout KwaZulu-Natal—the A4-sized Facility- held Record (FHR) and the small PHR (see Photograph 1). They are both called “Outpatient Record”. The FHRs are used only at that facility and are filed at the facility. The PHR is kept by the patient and can thus be used at any health facility.